2014
DOI: 10.3347/kjp.2014.52.6.661
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Helminths among Inhabitants of Cambodia (2006-2011)

Abstract: In order to investigate the status of intestinal helminthic infections in Cambodia, epidemiological surveys were carried out on a national scale, including 19 provinces. A total of 32,201 fecal samples were collected from schoolchildren and adults between 2006 and 2011 and examined once by the Kato-Katz thick smear technique. The overall egg positive rate of intestinal helminths was 26.2%. The prevalence of hookworms was the highest (9.6%), followed by that of Opisthorchis viverrini/minute intestinal flukes (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 14 publications
3
32
6
Order By: Relevance
“…Several molecular epidemiologic surveys have also reported that N. americanus and A. ceylanicum are the two most common hookworm species infecting humans and dogs in Asia. [6][7][8][9][10] Prevalences of hookworms in Cambodia are reportedly very high, 18 and are predominantly due to N. americanus and A. ceylanicum (51.6% equal prevalence): only 3.2% of people were found infected with A. duodenale. 6 In Thailand, the principal hookworm species infecting humans was confirmed as N. americanus.…”
mentioning
confidence: 99%
“…Several molecular epidemiologic surveys have also reported that N. americanus and A. ceylanicum are the two most common hookworm species infecting humans and dogs in Asia. [6][7][8][9][10] Prevalences of hookworms in Cambodia are reportedly very high, 18 and are predominantly due to N. americanus and A. ceylanicum (51.6% equal prevalence): only 3.2% of people were found infected with A. duodenale. 6 In Thailand, the principal hookworm species infecting humans was confirmed as N. americanus.…”
mentioning
confidence: 99%
“…Previous studies have shown high rates of hookworm and other helminth infections among Cambodian adults. 4,5 The Cambodian Ministry of Health recommends that pregnant women receive one dose of deworming treatment (mebendazole) after the first trimester 6 ; however, the benefit of this one dose (if taken) is in question as its efficacy appears low, with a cure (egg-negative after treatment) rate of only ∼18-36% for helminth infections in school-aged children in neighboring Lao People's Democratic Republic. 7 We acknowledge that the effectiveness of deworming treatments also largely depends on the types of parasitic infections present.…”
Section: Introductionmentioning
confidence: 99%
“…2 Hookworm infections are a major contributor to anemia and are endemic in Cambodia. 4 Humans contact hookworms through exposure to eggs and larvae in soil that is contaminated by fecal matter. Previous studies have shown high rates of hookworm and other helminth infections among Cambodian adults.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cambodia is located in southeast Asia and is divided into 24 provinces. 4 More than two-thirds of the population do not have access to improved sanitation facilities and clean drinking water. The main source of drinking water for most inhabitants is rainwater.…”
Section: Introductionmentioning
confidence: 99%